Corporate Zakat and Shareholders: Conceptual Analysis and Implementation - Efendi, Nur; Mukhlas, Oyo Sunaryo; Khosyi'ah, Siah (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This This article aims to analyze the conceptual framework of corporate zakat and critically examine its foundations in Islamic law and positive law, as well as the role of shareholders in corporate zakat decision-making. Furthermore, the article also explores the practical challenges in the implementation of corporate zakat in Indonesia.  In Islamic law, corporations are categorized as syakhshiyyah i’tibariyyah (legal persons), making them subject to zakat obligations similar to individuals. In Indonesia, various legal instruments formally recognize corporate zakat; however, implementation faces challenges such as low compliance, ineffective regulation, and limited shareholder participation. This study employs a normative qualitative approach, focusing on the examination of positive legal norms and Sharia values. The research is conducted through library research by reviewing contemporary fiqh literature, national legal documents, and corporate zakat practices in Indonesia. The collected data were then analyzed for their relevance and alignment with actual practices in the field, followed by evaluation and conclusion based on the results of the analysis. The findings highlight the need to enhance zakat literacy among shareholders, institutionalize zakat within corporate governance structures, and develop supportive public policy. The article recommends literacy campaigns, regulatory harmonization, and the integration of zakat into ESG frameworks as systemic strategies. It also calls for further research on zakat's role in value driven corporate governance transformation.